Pengaruh Computer Knowledge, Fasilitas Laboratorium, Computer anxiety, dan Motivasi Belajar terhadap Hasil Belajar Siswa SMK Negeri 2 Buduran - Intan Ratu Pratiwi; Agung Listiadi (Edunusa: Journal of Economics and Business Education, 2021)
This research indicates the influence of laboratory accounting, Computer Knowledge, computer anxiety, and the motivation to study on the students’ result of computer accounting in the XI Class of Buduran 2 Vocational High School. This study using multiple linear regression analysis techniques which is part of the kind of research ex-post facto calculation menggunakan.aplikasi spss 25 version. . The population of this study were all students of class XI majoring in Accounting at SMK Negeri 2 Buduran who visited 125 students. The results of the F-test show the acquisition of F-count (75.723) with a significance level (0.000), so it can be interpreted that Computer Knowledge, accounting laboratory facilities, computer anxiety, and learning motivation simultaneously affect computer accounting learning outcomes. The result of the t-test can demonstrate that 1) Computer Knowledge halfway significantly affects bookkeeping PC learning results 2) Laboratory offices in part significantly affect bookkeeping PC learning results 3) Computer anexiaty in part significantly affects bookkeeping PC learning results 4) Learning inspiration in part incomplete critical impact on bookkeeping PC learning results.